A method for preparing a ceramic sealing ring
By using ball milling technology of hyperbranched polyester and initiator and ceramic powder, a high solid content slurry is formed and sintered, the complex shape and uniformity problems in the preparation of ceramic seal rings are solved, and the high density and good ceramic seal rings are achieved. Mechanical properties.
Patent Information
- Application Number
- CN202411559922.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-11-04
AI Technical Summary
During the preparation of existing ceramic seal rings, it is difficult to prepare samples of complex shapes by dry press molding, and the internal uniformity of the ceramics is poor, which limits the mechanical properties of the material.
The second generation of hyperbranched polyester was obtained by reacting trimethylolpropane and 2,2-dihydroxymethylolpropane acid, combined with epoxychlorohydrin and tetrabutyl ammonium bromide, and after treatment with aqueous sodium hydroxide solution, it was added with the The agent and ceramic powder ball mill form a high solids content slurry, and the green body is obtained by vacuum degassing and mold curing, and then sintered under an inert atmosphere to form a ceramic seal ring with high density and good mechanical properties.
The rapid curing of ceramic sealing rings and the structural uniformity improvement are achieved, the slurry settlement is avoided, the density and mechanical properties of green and ceramic sealing rings are improved, and the complex structure of special-shaped sealing rings can be prepared.
Smart Images

Figure QLYQS_1 
Figure QLYQS_2
Abstract
Description
Technical Field
[0001] The present invention relates to the field of ceramic materials, in particular to a method for preparing a ceramic sealing ring. Background Art
[0002] The power battery is the "heart" of electric vehicles, and its service life and safety are considered crucial to their widespread adoption. The sealing performance of the end caps in power batteries is crucial to their safety. Ceramics offer superior electrical insulation and mechanical strength, and in recent years, leading battery companies have increasingly adopted ceramic seals in place of conventional plastic ones.
[0003] Ceramic sealing rings can give full play to the high insulation, high strength, high temperature resistance, aging resistance, corrosion resistance and other characteristics of ceramic materials. After metallization welding, they have good airtightness, are extremely resistant to high temperatures, can withstand rapid temperature changes, have high mechanical strength, and have small dimensional tolerances at the sealing point, greatly improving service life and safety.
[0004] Every step in the preparation process of ceramic sealing rings will affect its properties, among which the molding process is one of the important links, because the density and uniformity of the green body will directly affect the sintering performance of the material. Although the currently commonly used dry pressing molding method has the advantages of simple process and high efficiency, dry pressing molding is difficult to prepare samples of complex shapes, and due to the poor uniformity inside the ceramic green body, the mechanical properties are limited. Summary of the Invention
[0005] Purpose of the invention: In order to solve the above technical problems, the present invention proposes a method for preparing a ceramic sealing ring.
[0006] The technical solutions adopted are as follows:
[0007] A method for preparing a ceramic sealing ring is as follows:
[0008] S1: The second generation of hyperbranched polyester is obtained by reacting trimethylolpropane and 2,2-dimethylolpropionic acid;
[0009] S2: Mix the second-generation hyperbranched polyester, epichlorohydrin, and tetrabutylammonium bromide, raise the temperature to 40-60°C, react for 1-5 hours, add a sodium hydroxide aqueous solution, raise the temperature to 90-100°C, and continue to react for 1-5 hours. After returning to room temperature, wash the reaction solution with water until it is neutral, and remove small molecules by vacuum distillation to obtain a hyperbranched epoxy resin;
[0010] S3: first, adding an initiator and ceramic powder to ethanol and ball-milling them, then adding a hyperbranched epoxy resin and mixing them to obtain a slurry with a solid content of ≥60%. After vacuum degassing, the slurry is poured into a mold and solidified to obtain a green body;
[0011] S4: After drying the green body, remove the binder, heat it to 1450-1600℃ in an inert gas atmosphere and sinter it isostatically pressed for 1-5h, then cool it to 1200-1300℃ and anneal it for 1-5h, and finally cool it naturally to room temperature.
[0012] Furthermore, the molar ratio of trimethylolpropane to 2,2-dimethylolpropionic acid is 1:9.
[0013] Furthermore, the molar ratio of the second-generation hyperbranched polyester to epichlorohydrin is 1:12-20.
[0014] Furthermore, the amount of tetrabutylammonium bromide used is 0.1-1% of the mass of the second-generation hyperbranched polyester.
[0015] Furthermore, the initiator is aliphatic amine disulfide and aromatic amine disulfide;
[0016] The mass ratio of the aliphatic amine disulfide to the aromatic amine disulfide is 1-10:1-10.
[0017] Furthermore, the structural formula of the fatty amine disulfide is as follows:
[0018] ;
[0019] Wherein, n≥6, optionally 6, 7, 8, 9, 10, 11 or 12, and n is preferably 8.
[0020] Furthermore, the structural formula of the aromatic amine disulfide is as follows:
[0021] .
[0022] Furthermore, the aromatic amine disulfide is preferably 4,4'-diphenyldisulfide.
[0023] Furthermore, the ceramic powder includes aluminum oxide powder, yttrium oxide, copper oxide and lanthanum oxide;
[0024] The mass ratio of the aluminum oxide powder, yttrium oxide, copper oxide and lanthanum oxide is 95-100:1-5:0.1-1:0.1-1.
[0025] Furthermore, the mass ratio of the initiator, ceramic powder and hyperbranched epoxy resin is 0.1-0.5:60-80:1-5.
[0026] Furthermore, the pressure during isostatic sintering is 100-200 MPa.
[0027] Beneficial effects of the present invention:
[0028] The present invention provides a preparation method of a ceramic sealing ring. The hyperbranched epoxy resin prepared in the present invention has a more dispersed molecular structure and more active groups, can form a three-dimensional gel network with a high cross-linking density, thereby realizing faster rapid solidification of the slurry and effectively avoiding slurry sedimentation caused by an excessively long curing time, thereby improving the uniformity of the internal structure of the green body and improving its strength. An initiator composed of aliphatic amine disulfide and aromatic amine disulfide can undergo a curing reaction with the hyperbranched epoxy resin. The introduction of flexible aliphatic long chains can prevent the formation of microcracks in the green body caused by an excessively high cross-linking density. The aromatic amine disulfide can improve the structural stability of the green body and increase the strength of the green body. Since disulfide bonds are prone to bond breaking reactions, they can be quickly broken and decomposed during debinding and can be fully discharged in a short time, creating conditions for subsequent sintering and densification. The method of the present invention can be used to prepare special-shaped sealing rings with complex structures. The prepared green bodies and ceramic sealing rings have high density and good mechanical properties. DETAILED DESCRIPTION
[0029] Unless otherwise specified, the following examples and comparative examples were conducted in parallel, using the same processing steps and parameters.
[0030] Example 1:
[0031] This embodiment provides a method for preparing a ceramic sealing ring:
[0032] ;
[0033] S1: Under nitrogen protection, 2,2-dimethylolpropionic acid (3 mol, 402 g), trimethylolpropane (1 mol, 134 g), and p-toluenesulfonic acid (1.5 g) as a catalyst were added to a flask. The mixture was stirred and heated to 140°C for 3 h. During the reaction, water generated by the reaction was separated by a water separator. Then, 2,2-dimethylolpropionic acid (6 mol, 804 g) and p-toluenesulfonic acid (8 g) were added. The temperature was kept constant and the reaction was continued for 3 h. During the reaction, water generated by the reaction was separated by a water separator. The nitrogen was stopped, and a vacuum pump was connected to remove water under reduced pressure until no water was distilled out. After cooling to room temperature, the mixture was dissolved in an appropriate amount of acetone, recrystallized in toluene, filtered, and the obtained product was dried to obtain a second-generation hyperbranched polyester.
[0034] S2: The second-generation hyperbranched polyester (0.1 mol, 116.7 g), epichlorohydrin (2 mol, 185 g) and tetrabutylammonium bromide (0.6 g) were added to a flask with a condenser and stirred to mix. The mixture was heated to 60°C for 5 h, and then 10 ml of a 10 wt% aqueous sodium hydroxide solution was added. The mixture was heated to 100°C and the reaction was continued for 5 h. After returning to room temperature, the reaction solution was repeatedly washed with deionized water until neutral. Finally, small molecules were removed by distillation under reduced pressure to obtain a hyperbranched epoxy resin.
[0035] S3: Using 4,4'-diphenyldisulfide and 8,8-dioctyldisulfide as initiators in a mass ratio of 1:5, and alumina powder, yttrium oxide, copper oxide, and lanthanum oxide in a mass ratio of 98:2:0.5:0.5 as ceramic powders, the initiator, ceramic powder, and ethanol are added to a ball mill, and ball milled on a planetary ball mill for 5 hours. Then, a hyperbranched epoxy resin is added and quickly stirred to obtain a slurry with a solid content of 80%, wherein the mass ratio of the initiator, ceramic powder, and hyperbranched epoxy resin is 0.5:65:3. After vacuum degassing, the slurry is poured into a mold and cured at room temperature for 60 minutes to obtain a green body;
[0036] S4: After drying the green body in an oven at 80℃ for 24h, heat it to 800℃ at a rate of 1℃ / min and keep it warm for 2h to remove binder, then introduce argon protection, heat it to 1550℃ at a rate of 10℃ / min, isostatically press sinter it at 150MPa for 4h, then cool it to 1250℃ at a rate of 5℃ / min and keep it warm for 2h to anneal, and finally cool it naturally to room temperature.
[0037] Example 2:
[0038] This embodiment provides a method for preparing a ceramic sealing ring:
[0039] Wherein, S1 and S2 are the same as those in Example 1;
[0040] S3: Using 4,4'-diphenyldisulfide and 8,8-dioctyldisulfide in a mass ratio of 1:10 as initiators, and alumina powder, yttrium oxide, copper oxide, and lanthanum oxide in a mass ratio of 98:2:0.5:0.5 as ceramic powders, the initiator, ceramic powder, and ethanol are added to a ball mill, and ball milled on a planetary ball mill for 5 hours. Then, a hyperbranched epoxy resin is added and quickly stirred to obtain a slurry with a solid content of 80%, wherein the mass ratio of the initiator, ceramic powder, and hyperbranched epoxy resin is 0.5:65:3. After vacuum degassing, the slurry is poured into a mold and cured at room temperature for 60 minutes to obtain a green body;
[0041] S4: After drying the green body in an oven at 80℃ for 24h, heat it to 800℃ at a rate of 1℃ / min and keep it warm for 2h to remove binder, then introduce argon protection, heat it to 1550℃ at a rate of 10℃ / min, isostatically press sinter it at 150MPa for 4h, then cool it to 1250℃ at a rate of 5℃ / min and keep it warm for 2h to anneal, and finally cool it naturally to room temperature.
[0042] Example 3:
[0043] This embodiment provides a method for preparing a ceramic sealing ring:
[0044] Wherein, S1 and S2 are the same as those in Example 1;
[0045] S3: Using 4,4'-diphenyldisulfide and 8,8-dioctyldisulfide as initiators in a mass ratio of 5:1, and alumina powder, yttrium oxide, copper oxide, and lanthanum oxide in a mass ratio of 98:2:0.5:0.5 as ceramic powders, the initiator, ceramic powder, and ethanol are added to a ball mill, and ball milled on a planetary ball mill for 5 hours. Then, a hyperbranched epoxy resin is added and quickly stirred to obtain a slurry with a solid content of 80%, wherein the mass ratio of the initiator, ceramic powder, and hyperbranched epoxy resin is 0.5:65:3. After vacuum degassing, the slurry is poured into a mold and cured at room temperature for 60 minutes to obtain a green body;
[0046] S4: After drying the green body in an oven at 80℃ for 24h, heat it to 800℃ at a rate of 1℃ / min and keep it warm for 2h to remove binder, then introduce argon protection, heat it to 1550℃ at a rate of 10℃ / min, isostatically press sinter it at 150MPa for 4h, then cool it to 1250℃ at a rate of 5℃ / min and keep it warm for 2h to anneal, and finally cool it naturally to room temperature.
[0047] Example 4:
[0048] This embodiment provides a method for preparing a ceramic sealing ring:
[0049] Wherein, S1 and S2 are the same as those in Example 1;
[0050] S3: Using 4,4'-diphenyldisulfide and 8,8-dioctyldisulfide as initiators in a mass ratio of 10:1, and alumina powder, yttrium oxide, copper oxide, and lanthanum oxide in a mass ratio of 98:2:0.5:0.5 as ceramic powders, the initiator, ceramic powder, and ethanol are added to a ball mill, and ball milled on a planetary ball mill for 5 hours. Then, a hyperbranched epoxy resin is added and quickly stirred to obtain a slurry with a solid content of 80%, wherein the mass ratio of the initiator, ceramic powder, and hyperbranched epoxy resin is 0.5:65:3. After vacuum degassing, the slurry is poured into a mold and cured at room temperature for 60 minutes to obtain a green body;
[0051] S4: After drying the green body in an oven at 80℃ for 24h, heat it to 800℃ at a rate of 1℃ / min and keep it warm for 2h to remove binder, then introduce argon protection, heat it to 1550℃ at a rate of 10℃ / min, isostatically press sinter it at 150MPa for 4h, then cool it to 1250℃ at a rate of 5℃ / min and keep it warm for 2h to anneal, and finally cool it naturally to room temperature.
[0052] Comparative Example 1:
[0053] The process is substantially the same as Example 1, except that ethylene glycol diglycidyl ether of the same mass is used instead of the hyperbranched epoxy resin.
[0054] Comparative Example 2:
[0055] The process is substantially the same as Example 1, except that the hyperbranched epoxy resin is replaced by hydantoin epoxy resin of the same mass.
[0056] Comparative Example 3:
[0057] The process is substantially the same as Example 1, except that ethylenediamine of the same mass is used as the initiator instead of the combination of 4,4'-diphenyldisulfide and 8,8-dioctyldisulfide.
[0058] Comparative Example 4:
[0059] The process is basically the same as Example 1, except that the mass of the initiator remains unchanged and only 4,4'-dithiodiphenylamine is added.
[0060] Comparative Example 5:
[0061] The process is basically the same as Example 1, except that the mass of the initiator remains unchanged and only 8,8-dioctyldithioamine is added.
[0062] Performance testing:
[0063] According to the methods of Examples 1-4 and Comparative Examples 1-5 of the present invention, samples were prepared and performance tested;
[0064] The bulk density (g / cm) was determined using the Archimedes displacement method. 3 The three-point bending strength (MPa) was tested by an electronic universal testing machine with a test interval of 30 mm and a test rate of 0.5 mm / min. The fracture toughness (MPa·m 1 / 2 );
[0065] The test results are shown in Table 1 below:
[0066] Table 1:
[0067] ;
[0068] As can be seen from Table 1 above, the green body and ceramic sealing ring prepared by the method of the present invention both have a high density and good mechanical properties;
[0069] From the comparison of the data of Example 1 and Comparative Examples 1-2, it can be seen that the green body and ceramic sealing ring prepared by the hyperbranched epoxy resin in the present invention have higher density and better mechanical properties than those prepared by ethylene glycol diglycidyl ether and hydantoin epoxy resin;
[0070] From the comparison of the data of Example 1 and Comparative Examples 3-5, it can be seen that the green body and ceramic sealing ring prepared by using the combination of 4,4'-dithiodiphenylamine and 8,8-dithiodioctylamine as the initiator in the present invention have higher density and better mechanical properties.
[0071] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the various embodiments of the present invention.
Claims
1. A method for preparing a ceramic sealing ring, characterized in that: The details are as follows: S1: The second generation of hyperbranched polyester is obtained by reacting trimethylolpropane and 2,2-dimethylolpropionic acid; S2: Mix the second generation hyperbranched polyester, epichlorohydrin and tetrabutylammonium bromide, heat to 40-60°C and react for 1-5h, add sodium hydroxide aqueous solution, heat to 90-100°C and continue to react for 1-5h, return to room temperature, wash the reaction solution with water until it is neutral, and remove small molecules by reduced pressure distillation to obtain a hyperbranched epoxy resin; S3: firstly adding an initiator and a ceramic powder into ethanol for ball milling, then adding a hyperbranched epoxy resin and mixing well to obtain a slurry with a solid content of ≥60%, and then pouring the slurry into a mold for solidification after vacuum degassing to obtain a green body; S4: After the green body is dried and debinded, the temperature is raised to 1450-1600°C in an inert gas atmosphere for isostatic sintering for 1-5 hours, then the temperature is lowered to 1200-1300°C for annealing for 1-5 hours, and finally naturally cooled to room temperature.
2. The method for preparing a ceramic sealing ring according to claim 1, characterized in that: The molar ratio of the trimethylolpropane to the 2,2-dimethylolpropionic acid is 1:
9.
3. The method for preparing a ceramic sealing ring according to claim 1, characterized in that: The molar ratio of the second generation hyperbranched polyester to epichlorohydrin is 1:12-20.
4. The method for preparing a ceramic sealing ring according to claim 1, characterized in that: The amount of tetrabutylammonium bromide used is 0.1-1% of the mass of the second-generation hyperbranched polyester.
5. The method for preparing a ceramic sealing ring according to claim 1, characterized in that: The initiator is aliphatic amine disulfide and aromatic amine disulfide; The mass ratio of the aliphatic amine disulfide to the aromatic amine disulfide is 1-10:1-10.
6. The method for preparing a ceramic sealing ring according to claim 5, characterized in that: The structural formula of the fatty amine disulfide is as follows: ; Among them, n≥6.
7. The method for preparing a ceramic sealing ring according to claim 5, characterized in that: The structural formula of the aromatic amine disulfide is shown below: 。 8. The method for preparing a ceramic sealing ring according to claim 1, characterized in that: The ceramic powder includes aluminum oxide powder, yttrium oxide, copper oxide and lanthanum oxide; The mass ratio of the aluminum oxide powder, yttrium oxide, copper oxide and lanthanum oxide is 95-100:1-5:0.1-1:0.1-1.
9. The method for preparing a ceramic sealing ring according to claim 1, characterized in that: The mass ratio of the initiator, the ceramic powder and the hyperbranched epoxy resin is 0.1-0.5:60-80:1-5.
10. The method for preparing a ceramic sealing ring according to claim 1, characterized in that: The pressure during isostatic sintering is 100-200MPa.